2018
DOI: 10.1186/s12889-018-5823-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with treatment delay among newly diagnosed tuberculosis patients in Dessie city and surroundings, Northern Central Ethiopia: a cross-sectional study

Abstract: BackgroundDelayed treatment of tuberculosis (TB) cases increases the risk of death and rate of infection in the community. Early diagnosis and initiation of treatment is essential for effective TB control. The aim of this study was to assess length of delays and analyze predictors of treatment delay of newly diagnosed TB patients.MethodsA cross-sectional study was conducted in Dessie city and surroundings from April1, 2016 to January 30, 2017. Fifteen health facilities of study area were selected randomly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 30 publications
15
66
2
Order By: Relevance
“…The finding from various studies indicate that treatment delay may be influenced by several factors, namely lack of knowledge, lack of awareness of the significance of symptoms, negative social attitudes or combinations of these. 18,38 Our findings are also in congruence with of several other studies among health professions students. Kilicaslan et al assessed the impact of TB training on medical students at Istanbul Medical School.…”
Section: Discussionsupporting
confidence: 92%
“…The finding from various studies indicate that treatment delay may be influenced by several factors, namely lack of knowledge, lack of awareness of the significance of symptoms, negative social attitudes or combinations of these. 18,38 Our findings are also in congruence with of several other studies among health professions students. Kilicaslan et al assessed the impact of TB training on medical students at Istanbul Medical School.…”
Section: Discussionsupporting
confidence: 92%
“…Accessibility to health services and awareness about TB might influence their early health-seeking behavior and follow-up after the first visit to the health facility. The health system delay could also amplify the total delay and TB transmission rate [43]. The health system's delay in the present study seems to primarily be related to a referral from a lower level to higher level health system for further investigations.…”
Section: Discussionmentioning
confidence: 66%
“…Studies from Asia have reported stigma and limited knowledge among health practitioners as obstacles in the uptake of preventive, diagnostic and treatment services among HBV patients (4,23). Delayed health seeking behaviour has been widely reported in tuberculosis and is a result of several factors such as lack of symptoms, low patient knowledge, practising self-medication, and the use of traditional healing methods (24)(25)(26). In our study, the asymptomatic nature of HBV, poverty and lack of knowledge (including among healthcare workers) were challenges in accessing timely and appropriate healthcare (27).…”
Section: Stigmamentioning
confidence: 99%